2009
DOI: 10.1029/2008gl036571
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the Middle Miocene Climate Optimum

Abstract: [1] Proxy data constraining land and ocean surface paleotemperatures indicate that the Middle Miocene Climate Optimum (MMCO), a global warming event at $15 Ma, had a global annual mean surface temperature of 18.4°C, about 3°C higher than present and equivalent to the warming predicted for the next century. We apply the latest National Center for Atmospheric Research (NCAR) Community Atmosphere Model CAM3.1 and Land Model CLM3.0 coupled to a slab ocean to examine sensitivity of MMCO climate to varying ocean hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
170
0
7

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(186 citation statements)
references
References 34 publications
9
170
0
7
Order By: Relevance
“…According to numerical simulation of You et al (2009), the global annual mean surface temperature at around 15 Ma were about 3°C higher than today, and the meridional temperature gradient on the northern hemisphere was less pronounced than present. Indeed, European mid-latitudes proxy-data for that time indicate 9 to 12°C warmer temperatures in the annual mean than today (Böhme, 2003;Mosbrugger et al, 2005;Ivanov and Böhme, in press).…”
Section: Discussionmentioning
confidence: 99%
“…According to numerical simulation of You et al (2009), the global annual mean surface temperature at around 15 Ma were about 3°C higher than today, and the meridional temperature gradient on the northern hemisphere was less pronounced than present. Indeed, European mid-latitudes proxy-data for that time indicate 9 to 12°C warmer temperatures in the annual mean than today (Böhme, 2003;Mosbrugger et al, 2005;Ivanov and Böhme, in press).…”
Section: Discussionmentioning
confidence: 99%
“…Most of them investigated the impact of varying pCO 2 on middle Miocene climate, and concluded that high pCO 2 is necessary to simulate climatic conditions consistent with data-based reconstructions (Tong et al, 2009;You et al, 2009;Henrot et al, 2010;Krapp and Jungclaus, 2011;Hamon et al, 2012). Henrot et al (2010) and Herold et al (2009) also performed sensitivity experiments on palaeogeography, but they did not study the impact of the eastern Tethys seaway closure.…”
Section: N Hamon Et Al: Tethys Seaway Closure and Middle Miocene CLmentioning
confidence: 99%
“…The Miocene climate exhibited marked changes including the Mid-Miocene Climatic Optimum (MMCO, *15-17.0 Ma [2]) during which temperatures were inferred to be *3-8°C higher than preindustrial level [3,4]. The mechanisms leading to the MMCO are still debated [2], but evidence points to an increase in the concentration of atmospheric CO 2 [4].…”
Section: Introductionmentioning
confidence: 99%